2014
DOI: 10.1177/0961203314558861
|View full text |Cite
|
Sign up to set email alerts
|

Altered glycosylation of complexed native IgG molecules is associated with disease activity of systemic lupus erythematosus

Abstract: In addition to the redundancy of the receptors for the Fc portion of immunoglobulins, glycans result in potential ligands for a plethora of lectin receptors found in immune effector cells. Here we analysed the exposure of glycans containing fucosyl residues and the fucosylated tri-mannose N-type core by complexed native IgG in longitudinal serum samples of wellcharacterized patients with systemic lupus erythematosus. Consecutive serum samples of a cohort of 15 patients with systemic lupus erythematosus during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 47 publications
4
46
1
4
Order By: Relevance
“…In a very recent study of a small number of SLE patients (n = 15), Sjowall and colleagues showed increased binding of lectins recognizing fucose to complexed natural IgG in patients with active disease . This contradicts our observation that IgG fucosylation is decreased in SLE patients.…”
Section: Discussioncontrasting
confidence: 85%
“…In a very recent study of a small number of SLE patients (n = 15), Sjowall and colleagues showed increased binding of lectins recognizing fucose to complexed natural IgG in patients with active disease . This contradicts our observation that IgG fucosylation is decreased in SLE patients.…”
Section: Discussioncontrasting
confidence: 85%
“…22 In 2015, we reported on the impact of fucosyl exposure on native circulating IgG complexes in patients with SLE. 43 Our results showed significantly higher levels of AAL and LCA binding sites exposed on IgG complexes of patients with SLE than on those of normal healthy donors (Figure 1). Moreover, disease activity in patients positively correlated with exposure of AAL-reactive fucosyl residues on immobilized IgG complexes.…”
Section: Fucosylationmentioning
confidence: 51%
“…Similarly, complexes consisting of antibodies against CRP have been described in lupus nephritis [38]. In contrast to SLE [23], CRP itself appears to associate with IgG in RA. CRP is elevated chronically in RA and has shown to contribute to bone destruction [39].…”
Section: Discussionmentioning
confidence: 86%
“…Composition of native immunoglobulin (Ig)G complexes and their putative glycosylation sites. This scheme shows (1) the canonical glycans attached to the IgG–CH2‐domain, (2) the glycans attached to some VH and CH1 domains, (3) putative sites of hyper‐glycosylation, (4) increased accessibility for lectin binding of the canonical glycans attached to the CH2‐domains and (5) that glycans can also be exposed by IgG‐associated molecules exemplified by IgA, IgM, C1q, C3d and C‐reactive protein (CRP).…”
mentioning
confidence: 99%